THE PEMBERIAN CORE STABILITY EXERCISE LEBIH MENINGKATKAN KESEIMBANGAN STATIS DARIPADA BALANCE BEAM EXERCISE PADA SISWA SEKOLAH DASAR NEGERI 11 SUMERTA DENPASAR - Santi Bery Hastuti; Ari Wibawa; I Made Muliarta (Majalah Ilmiah Fisioterapi Indonesia, 2015)
OBJECTIVE: To determine the effectiveness of increasing from the static balance on the intervention of core stability exercise compare with balance beam exercise. SUBJECT: 30 healthy subjects, divided randomly into 2 group. Each group consist of 15 subjects. Group I gets the core stability exercise, while Group II gets the balance beam exercise. RESEARCH PLACE: Sekolah Dasar Negeri 11 Sumerta Denpasar. RESEARCH TIME: 20 Agustus-22 September 2014. MEASURING INSTRUMENT: Stork Stand Test. RESEARCH DESIGN: The research is an experimental study with pre test and post test control group design. RESULT: Each group conduct the normaly data test using Shapiro-Wilk Test Group I’s score before treatment is p>0,05, which means that the data has normal distribution. After treatment, Group I is score is p<0,05 which means that the data has abnormal distribution. Group II’s score before and after treatment’s p>0,05 which means that the data has normal distribution. Group I using Wilcoxon Match Pair Test gets p<0,05 which means there are significant difference of the static balance score between before and after treatment with core stability exercise. Group II using Paired Sample T-Test gets p<0,05 which means there are significant difference of the static balance score between before and after treatment with balance beam exercise. Differentiation test using Mann Whitney U Test on both groups shows p<0,05 which means there are significant difference between Group I and Group II on increasing the static balance. CONCLUSION: Based on the data analisation and the discussion that has been done, we can conclude that the intervention of core stability exercise increase the static balance more than Balance Beam Exercise.